A pilot phylogeny study of Nemobiinae inferred from 18S, 28s and COI genes, with descriptions of two new genera and a new species from Hainan, China (Orthoptera: Grylloidea: Trigonidiidae) - Shen, Chu-Ze; Guo, Pei-Kun; He, Zhu-Qing (Zootaxa, 2020)
The phylogenetic tree of Chinese Nemobiinae species was reconstructed based on one mitochondrial COI fragment and two nuclear ribosomal loci (18S and 28S). According to both of concatenated and coalescent trees, Dianemobius, Polionemobius and Pteronemobius (except P. jianfenglingensis Liu & Shi) were shown to be monophyletic with highly nodal supports. As to P. jianfenglingensis, it should be moved into a newly established genus, Giganemobius Shen & He gen. nov. In addition, a new mute species named as Qionemobius hsterus Shen & He gen. nov. & sp. nov. was reported. It differs from other genera by having six apical spurs on hind tibia, but lacking forewings. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).